New species of Exetasis (Diptera: Acroceridae) from Caparaó National Park, with a key to species of the genus - Lovati, Monara Santos; Alves, Amélia Ferreira (Acta Biológica Paranaense, 2023)
Exetasis caparaoensis Lovati sp. nov. (Acroceridae) is described from Brazil and a dichotomous key to species of Exetasis Walker is provided.